Disability and Quality of Life among People Living With HIV/AIDS in Ibadan, Nigeria (2017)
Background: Improvements in medical and pharmacologic management of HIV/AIDS has led to increased life expectancy for the afflicted individuals. Hence, the focus of management for People Living With HIV/AIDS (PLWHA) has shifted to issues relating to function and Quality of Life (QoL). Information is scarce on disability issues and quality of life among people living with HIIV/AIDS in Nigeria. This was the premise of this study that assessed the level of disability and how it related to quality of life among people living with HIV/AIDS in Ibadan, the largest city in Nigeria. Methods: 360 PLWHA (274 females; 86 males) aged 37.79±9.37 years participated in this study. They were recruited from the anti-retroviral clinics of one secondary and one tertiary healthcare facilities in Ibadan, Nigeria. Disability and QoL were assessed using the 12-item WHO Disability Assessment Schedule (WHODAS 2.0) and the WHOQOL_HIV Bref respectively. Data were analysed using Chi square and Kruskal Wallis test at p = 0.05. Results: Almost a quarter (23.6%) reported being currently ill, with HIV/AIDS-related symptoms accounting for the highest perceived illness (42.5%). Majority of these participants (71.1%) had mild to extreme disabilities. There were no significant associations (p > 0.05) between disability and each of age, sex and employment status. Disability was however, significantly associated with level of education, alcohol use, CD4 count, history of tuberculosis and QoL (p<0.005) between disability and each of age, sex and employment status. Disability was however, significantly associated with level of education, alcohol use, CD4 count, history of tuberculosis and QoL (p<0.001) Conclusion: Disability was relatively high among people living with HIV/AIDS in Ibadan, Nigeria. Although mostly rated mild, disability was associated with poor QoL. This underscores the need for early identification of disability in people living with HIV/AIDS to minimise its impact on their QoL.